Tools Are Needed to Promote Sedation Practices for Mechanically Ventilated Patients - Wang, Tao; Zhou, Dongxu; Zhang, Zhongheng; Ma, Penglin (Frontiers in Medicine, 2021)
Suboptimal sedation practices continue to be frequent, although the updated guidelines for management of pain, agitation and delirium in mechanically ventilated (MV) patients has been published for several years. The low adherence to the recommended minimal sedation strategy is multifactorial. However, the barriers to translation of this outcome favored strategy into usual care for MV patients remains under interpreted yet. In our view, it is necessary to reveal fresh insight into the interaction between the nociceptive stimuli what patients experienced and the individualized regulation of patient’s tolerability by using analgesics and sedatives. By better understanding this interaction, development of novel tools to assess patient tolerability, to define and predict over-sedation, or delirium will be expected for promotion of sedation practices in future.